PENGUATAN KEGIATAN KEAGAMAAN DAN SOSIAL BERBASIS POSDAYA MASJID DI DESA PAKISAN TLOGOSARI BONDOWOSO - Khoirul Ulum (BHAKTI: JURNAL PENGABDIAN DAN PEMBERDAYAAN MASYARAKAT, 2023)
The focus of the mentoring activities carried out by the team is to revive religious activities in the Pakisan Village mosque with the hope that there are other functions for the mosque besides just a place of worship. This program was carried out because we saw the condition of the mosque and prayer room in Pakisan Village, which apart from experiencing a decrease in the quantity of worshipers, also experienced a decrease in the intensity of other activities. The result of the implementation is that mosque-based POSDAYA brings several benefits such as strengthening religious activities and the emergence of public awareness that mosques are not just places of worship but can also carry out beneficial community activities. UMKM development and health improvement can also be carried out in the mosque environment to help economic growth and awareness of healthy lifestyles.